Reaction dynamics and residue identification of haemoglobin modification by acrolein, a lipid-peroxidation by-product - Lassé, Moritz; Stampfli, Anja R.; Orban, Thomas; Bothara, Roshit K.; Gerrard, Juliet A.; Fairbanks, Antony J.; Pattinson, Neil R.; Dobson, Renwick C.J. (Biochimica et biophysica acta. General subjects, 2021)
Abstract Lipid hydroperoxides decompose to reactive aldehydes, such as acrolein. Measurement of oxidative stress markers in the clinic could improve risk stratification for patients. To aid the development of diagnostic oxidative stress markers, we defined the acrolein modifications of haemoglobin using mass spectrometry. Acrolein modifications have little effect on the secondary structure of haemoglobin. They do not disrupt the quaternary structure, but instead promote crosslinked octamers. For acrolein modified haemoglobin the response to O2 binding is altered such that cooperativity is lost. Mass spectrometry experiments at a 1:1 acrolein:haemoglobin molar ratio demonstrate that the α-chain quickly forms an aza-Michael adduct (+56 Da), which then forms a more stable adduct, Nε-(3-methylpyridinium)lysine (MP-lysine, +76 Da) over 7 days. The β-chain remains relatively unchanged over the duration of the 7 days and the aza-Michael adduct is dominant. At 2:1 and 5:1 molar ratios the α-chain was consistently modified at K7, H20, H50, and the β-chain at C93 and H97 with the aza-Michael adduct. Beyond 5 h, an MP-adduct (+76 Da) was located predominantly at K7 of the α-chain, while an FDP-adduct (+94 Da) was observed at K95 of the β-chain. We have generated qualitative evidence identifying the acrolein target sites on haemoglobin, a potential oxidative stress marker that is easily measured in circulation. We provide data for the community to develop targeted mass spectrometric or immunometric assays for acrolein modified haemoglobin to further validate the potential of haemoglobin as an oxidative stress marker in patients . [Display omitted] •Acrolein extensively modifies haemoglobin lysine, histidine and cysteine residues.•Acrolein adducts induce crosslinking and alters haemoglobin cooperativity.•MP-lysine is consistently identified on residue αK7.•FDP-lysine is consistently identified on residue βK95.